In Vitro Effect of Mitochondria-Targeted Triphenylphosphonium-Based Compounds (Honokiol, Lonidamine, and Atovaquone) on the Platelet Function and Cytotoxic Activity - Montecino-Garrido, Héctor; Méndez, Diego; Araya-Maturana, Ramiro; Millas-Vargas, Juan Pablo; Wehinger, Sergio; Fuentes, Eduardo (Frontiers in Pharmacology, 2022)
Introduction: Obtaining triphenylphosphonium salts derived from anticancer compounds to inhibit mitochondrial metabolism is of major interest due to their pivotal role in reactive oxygen species (ROS) production, calcium homeostasis, apoptosis, and cell proliferation. However, the use of this type of antitumor compound presents a risk of bleeding since the platelet activation is especially dependent on the mitochondrial function. In this study, we evaluated the in vitro effect of three triphenylphosphonium-based compounds, honokiol (HNK), lonidamine (LDN), and atovaquone (ATO), on the platelet function linked to the triphenylphosphonium cation by a lineal 10-carbon alkyl chain and also the decyltriphenylphosphonium salt (decylphos). Methods: Platelets obtained by phlebotomy from healthy donors were exposed in vitro to different concentrations (0.1–10 μM) of the three compounds; cellular viability, exposure of phosphatidylserine, the mitochondrial membrane potential (∆Ψm), intracellular calcium release, and intracellular ROS generation were measured. Platelet activation and aggregation were induced by agonists (adenosine diphosphate, thrombin receptor-activating peptide-6, convulxin, or phorbol-12-myristate-13-acetate) and were evaluated by flow cytometry and light transmission, respectively. Results: The three compounds showed a slight cytotoxic effect from 1 μM, and this was concomitant with a decrease in ∆Ψm and intracellular calcium increase. Only ATO produced a modest but significant increase in intra-platelet ROS. Also, the three compounds increased the exposure to phosphatidylserine in platelets expressed in platelets positive for annexin V. None of the compounds had an inhibitory effect on the aggregation or activation markers of platelets stimulated with three different agonists. Similar results were obtained with decylphos. Conclusion: Triphenylphosphonium derivatives showed slight platelet toxicity below 1 μM, probably associated with their effect on ∆Ψm and exposure to phosphatidylserine, but no significant effect on platelet activation and aggregation, making them an antitumoral alternative with a low risk of bleeding. However, future assays on animal models and human trials are required to evaluate if their effects with a low risk for hemostasis are replicated in vivo.